NOT NINE BUT EIGHTEEN: Husein Muhammad on Aisha’s Marriage Age - Jahroh, Siti (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2022)
The minimum age for marriage in fiqh has been a debated issue. This minimum limit is typically interpreted with reference to Aisha's marriage to the Prophet. Husein Muhammad argued, contrary to popular belief that Aisha's age at the time of her marriage was eighteen, not nine. This paper explains the characteristics of Husein's views on the minimum age for marriage in Islam. The data was collected from reviews of Husein's and other researchers' works in which they discussed Husein's ideas. This paper argues that, according to Husein, it is demonstrably untrue to postulate that Aisha was nine years old when she married. Husein concluded that Aisha was at least eighteen when she wed the Prophet. This interpretation arises as a result of his comparison between Aisha's age and Asma's. Besides that, Husein also considers the maqāṣid syarīah principle, according to which the age of eighteen is the minimum age that is physically and psychologically ideal and more compatible with the soul preservation of women and their future offspring.[Batas usia minimum perkawinan dalam fikih tidak ditetapkan secara pasti. Interpretasi batas minimum ini biasanya merujuk pada riwayat perkawinan Sitti Aisyah dengan Nabi. Berbeda dengan pendapat umumnya, Husein Muhammad berargumen bahwa usia Sitti Aisyah pada saat menikah adalah delapan belas tahun, bukan sembilan tahun. Beranjak dari ini, paper ini menjelaskan bagaimana karakteristik pemikiran Husein tentang batas usia minimum perkawinan dalam Islam. Data dikumpulkan dari telaah literatur yang ditulis langsung oleh Husein dan peneliti lain yang membahas pemikirannya. Paper ini berargumen bahwa menurut Husein, tidak benar jika dikatakan bahwa usia Sitti Aisyah ketika menikah dengan Nabi Muhammad Saw adalah sembilan tahun. Melainkan Husein berkesimpulan bahwa Sitti Aisyah setidaknya berusia delapan belas tahun saat menikah dengan Nabi. Interpretasi ini muncul karena dalam pemikirannya ia berkaca pada data sejarah perbandingan Usia Sitti Aisyah dan Usia Asma. Selain itu, Husein dalam pemikirannya tidak terlepas dari pendekatan maqāṣid syarīah, di mana usia delapan belas tahun ia tafsirkan sebagai usia minimal yang paling ideal secara fisik dan psikis dan paling sesuai dengan pemeliharaan jiwa perempuan dan keturunannya kelak.]